The Role of Graciloplasty in the Treatment of Obstetric Anal Sphincter Injury with Subsequent Fecal Incontinence and Recurrent Low Recto-Vaginal Fistula: A Case Report - Alessandro Bergna; Jacques Megevand; Giacomo Mori; Leonardo Lenisa; Andrea Rusconi (Reports)
Background and Clinical Significance: Recto-vaginal fistulae (RVF) and fecal incontinence (FI) pose significant challenges for colorectal surgeons. Various therapeutic options have been proposed for each condition over time. Despite its procedural complexity and the risk of complications, graciloplasty remains a viable therapeutic option for both conditions, with favorable long-term results. To our knowledge, this is the first report of a case where the need to treat both conditions concurrently arose. Case Presentation: We report the case of a 54-year-old woman with severe FI and repeatedly operated on recurrent recto-vaginal fistula. The patient underwent graciloplasty to provide healthy tissue with an adequate vascular supply to both enhance the healing process of the fistula and reshape the anal canal with a circular muscular structure. Following the procedure, the patient experienced prompt symptom resolution and good clinical and functional recovery at a 1-year follow-up evaluation. Conclusions: This case report highlights the safety and effectiveness of an overlooked procedure for the treatment of large sphincter defects and concurrent recto-vaginal or recto-vaginal tears.